2009
DOI: 10.1021/la903641k
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mineralization of CaCO3on a Phospholipid Monolayer: From an Amorphous Calcium Carbonate Precursor to Calcite via Vaterite

Abstract: A phospholipid monolayer, approximately half the bilayer structure of a biological membrane, can be regarded as an ideal model for investigating biomineralization on biological membranes. In this work on the biomimetic mineralization of CaCO(3) under a phospholipid monolayer, we show the initial heterogeneous nucleation of amorphous calcium carbonate precursor (ACC) nanoparticles at the air-water interface, their subsequent transformation into the metastable vaterite phase instead of the most thermodynamically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Examples of these molecules are amino acids, polysaccharide, and proteins. 36 Because we also observed that bacterial surface charge did not affect amorphous silica transformation, it is possible that the surface energy of phospholipid membranes promotes the phase transformation of amorphous silica. In the present study, the surfaces of both Gram-positive and -negative bacteria are observed to promote the transformation of amorphous silica.…”
Section: Discussionmentioning
confidence: 66%
“…Examples of these molecules are amino acids, polysaccharide, and proteins. 36 Because we also observed that bacterial surface charge did not affect amorphous silica transformation, it is possible that the surface energy of phospholipid membranes promotes the phase transformation of amorphous silica. In the present study, the surfaces of both Gram-positive and -negative bacteria are observed to promote the transformation of amorphous silica.…”
Section: Discussionmentioning
confidence: 66%
“…The precipitation profile obtained by the ion activity product (Ca 2+ )(CO 3 2-), in the performed experiments with calciumacetate and starch (shown in Figs. 5.1a, 5.1c, 3a and 5.3c), suggests the common pattern of CaCO 3 precipitation with initial formation of less stable polymorphs and the subsequent ripening to the calcite precipitate (Gebauer & Cölfen, 2011;Xiao et al, 2009). Studying the type of CaCO 3 precipitate by comparing the ion activity product of Ca 2+ and CO 3 2-ions to the solubility products of the polymorphs were done in the previous studies as well (Gebauer & Cölfen, 2011;Lindeboom et al, 2013;Nehrke, 2007;Sawada, 1997).…”
Section: Kinetics Of Caco 3 Precipitation In a Single-stage Anaerobicmentioning
confidence: 88%
“…Vaterite's transformation to the most stable calcite is inhibited by the incorporation of organic compounds that became entangled during precipitation (Xiao et al . ; Natoli et al . ) in close vicinity of the cells or from the cell wall itself.…”
Section: Discussionmentioning
confidence: 99%